INVESTIGASI MINAT STUDI BREVET PAJAK PADA MAHASISWA AKUNTANSI DI STIE BINA BANGSA - Mochamad Fahru Komarudin; Raden Irna Afriani (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this study was to investigate the influence of career motivation and motivation analysis of interest in the study of brevet tax on students semester 7 Accounting academic year 2016/2017 at STIE Bina Bangsa. Research done in the environment STIE Bina Bangsa. These studies use quantitative methods (questionnaire). The population in this research 274 students. With a sample of as many as 100 students. Sample collection method using the technique of Accidental sampling. Data analysis technique used was multiple linear regression analysis. Based on the results of hypothesis testing on this research shows that economic motivation and career motivation to study interest Tax Brevet. This has the sense that career motivation to get the job interest to be eligible to study tax brevet. So did the economic motivation to be able to have an economic life be eligible without relying on others to study interest brevet.